Blended human-technology service realities in healthcare - Dodds S; Russell-Bennett R; Chen T; Oertzen A-S; Salvador-Carulla L; Hung Y-C (Emerald)
Purpose – The healthcare sector is experiencing a major paradigm shift toward a people-centered approach. The key issue with transitioning to a people-centered approach is a lack of understanding of the ever-increasing role of technology in blended human-technology healthcare interactions and the impacts on healthcare actors’ well-being. The purpose of the paper is to identify the key mechanisms and influencing factors through which blended service realities affect engaged actors’ well-being in a healthcare context. Design/methodology/approach – This conceptual paper takes a human-centric perspective and a value co creation lens and uses theory synthesis and adaptation to investigate blended human-technology service realities in healthcare services. Findings – The authors conceptualize three blended human-technology service realities – human-dominant, balanced and technology-dominant – and identify two key mechanisms – shared control and emotional-social and cognitive complexity – and three influencing factors – meaningful human-technology experiences, agency and DART (dialogue, access, risk, transparency) – that affect the well-being outcome of engaged actors in these blended human-technology service realities. Practical implications – Managerially, the framework provides a useful tool for the design and management of blended human-technology realities. The paper explains how healthcare services should pay attention to management and interventions of different services realities and their impact on engaged actors. Blended human-technology reality examples – telehealth, virtual reality (VR) and service robots in healthcare – are used to support and contextualize the study’s conceptual work. A future research agenda is provided. Originality/value – This study contributes to service literature by developing a new conceptual framework that underpins the mechanisms and factors that influence the relationships between blended human technology service realities and engaged actors’ well-being
Keywords: Blended human-technology service realities; People-centered healthcare; Shared control; DART; Well-being; Service robot; Covid-19